PENGARUH RASIO KEUANGAN, CORPORATE GOVERNANCE, DAN MAKROEKONOMI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN YANG TERDAFTAR DI INDONESIA STOCK EXCHANGE TAHUN 2014-2018 - RISKA ADINDA, AINUN; MUSDHOLIFAH, (Jurnal Ilmu Manajemen (JIM), 2020)
Stakeholders should understand the financial distress prediction of a company as an early warning system for the possibility of bankruptcy in the future. This study aims to examine the effect of financial ratios that are proxied by debt to assets ratio (DAR) and total assets turnover (TATO), corporate governance with the proxy for institutional ownership (KEPINS), managerial ownership (KEPMAN), board size (UKDEDIR), and macroeconomics proxied by inflation (INF) and exchange rates (NT) on the financial distress prediction. The parameter used to measure financial distress is the Taffler model. The period of this study for 5 years from 2014 to 2018. The population of this study is 224 infrastructure, utilities & transportation and trade, services & investment sector companies listed on the Indonesia Stock Exchange. Purposive sampling is used to select 56 companie samples in this study that analyzed using logistic regression. Processing research data analysis using the SPSS version 18. The results show that financial ratios have an effect on financial distress, specifically debt to asset ratio is significantly positive and total assets turnover is significantly negative on financial distress. Corporate governance and macroeconomics variable do not affect on financial distress. This shows that financial ratios are a barometer of financial health. The company must control debt and properly utilize the assets because this can cause financial distress. Keywords: corporate governance; financial distress; financial ratio; macroeconomics.